TANTANGAN DAN STRATEGI GURU DALAM MENYEIMBANGKAN TUGAS MENGAJAR DAN PEMBINAAN EKSTRAKURIKULER DI SEKOLAH DASAR - Setia Wati; Aryudawati; Yunani.H; Nasrul Asmawan; Urip sulistiyo; Ekasastrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to systematically explore the fundamental challenges and effective strategies implemented by elementary school teachers in achieving an optimal balance between their primary teaching duties in the classroom and their responsibilities in fostering extracurricular activities. This study employed a qualitative approach with a case study method to analyze the teachers' lived experiences. Data were collected through observation, in-depth interviews, and document analysis related to time management and curriculum. The results revealed several key challenges, such as tight time management, high administrative burden, physical and mental exhaustion, and limited resources. Schedule conflicts between core lessons and extracurricular activities often posed a significant obstacle. To address these challenges, teachers implemented several effective strategies. These strategies included: (1) careful planning and scheduling; (2) delegation of tasks and collaboration with fellow teachers or parents; (3) utilization of technology to improve administrative efficiency; and (4) development of stress management skills. In conclusion, although balancing teaching duties and fostering extracurricular activities is a complex challenge, teachers can manage it effectively with well-planned strategies and support from the school. This study recommends more flexible school policies and adequate resource allocation to support teachers' dual roles